Lean Six Sigma in a service context: a multi‐factor application approach in the telecommunications industry - Alexandros Psychogios; Jane Atanasovski; Loukas K Tsironis (2012)
Purpose: The purpose of this paper is to investigate issues related to the application of Lean Six Sigma (L6σ) in a service industry. By adopting a case‐study approach this paper analytically explores the critical success factors that affect L6σ implementation. Design/methodology/approach: The study adopts a qualitative approach attempting to explore the nature of L6σ application in a service context. In particular, two case studies from the telecommunications industry have been selected. Secondary data were collected through an analysis of companies' documents, written procedures and quality assurance policies. Moreover, primary data were collected through a number of interviews with managers and quality experts. Findings: There are particular factors that influence the implementation of L6σ in organizations, that can be distinguished in facilitators like Top Management Involvement & Support, Quality‐driven Organizational Culture, Quality‐driven Training, Top Down & Bottom Up Project Selection, Customer Satisfaction, Prior implementation of other quality improvement programs and Supportive Performance Management & IT Systems, and inhibitors such as Lack of Awareness for L6σ, Lack of Awareness for the Need of Continuous Quality Improvement Programs & L6σ, Lack of Strategic Orientation, Working Mentality & Habits. Research limitations/implications: The main limitation of the study is the fact that in both cases only managers and top administrators were approached. Frontline employees who are directly involved in L6σ approach may offer a clearer view on issues related to the impact of critical factors on L6σ application. Originality/value: This study has four major advantages. First, it expands our understanding regarding the implementation of L6σ in a service industry, in which the application of management models is more complex and problematic. Second, it focuses on the responses of managers, who always play the most significant role in the adoption of such techniques. Third, it explores the quality management initiatives in the telecommunications industry. Finally, it provides future studies with a L6σ multi‐factor application approach that can be further tested and developed.